ALTERNATIVE REINFORCEMENT AND ACTIVITY-BASED LEARNING (ARAL): USING CONTEXTUALIZED TOOLS TO DEVELOP WRITING SKILLS IN FILIPINO - Dayag, Edward Haze (International Journal of Business, Law, and Education, 2022)
This study analyzed the effectiveness of Alternative Reinforcement and Activity-based Learning (ARAL) in improving the writing skills in Filipino of the TVL students. This study addresses the Republic Act. No. 10533 encouraging the development and reproduction of instructional materials. This study used a pretest-posttest design. This design used four steps. The first step is to identify student respondents who are taking Filipino subject with specialization in technical-vocational track. The second step is to give the pretest to the students. The third step is to apply the learning intervention, Project ARAL. And the fourth step is to give a posttest. The mean score of the pre-test and post-test are both analyzed in this research. Overall, the use of Project ARAL can be used effectively to enhance students' ability to write technical-vocational writings using Filipino language. Lastly, there was a significant difference between the pre-test and post-test performed by the students.